A holistic perspective on corporate sustainability from a management viewpoint: Evidence from Japanese manufacturing multinational enterprises. (10th April 2019) - Ike, Masayoshi; Donovan, Jerome Denis; Topple, Cheree; Masli, Eryadi Kordi
Abstract: This study investigates what issues are considered by Japanese manufacturing multinational enterprises to be related to corporate sustainability when deciding on the location or significant expansion of their subsidiaries. Focusing on the developing countries of the Philippines, Indonesia, Thailand and Vietnam where there are significant Japanese manufacturing activities in an environmentally sensitive region, in-depth interviews were carried out with 58 representatives from 16 Japanese manufacturing multinational enterprises. Results identify that these multinational enterprises considered four main issue areas including the environment (waste material/water; air pollution; water supply; noise; green procurement), host country employment (size of workforce; above minimum wages; rights to association; women employment/empowerment; worker safety), workforce quality (experience/training; local employment) and local consumer benefits (product benefits/impact on lifestyle) as being related to corporate sustainability issues beyond purely commercial drivers. Host country regulations had a notable impact on the issues considered by the multinational enterprises, although some voluntarily moved beyond what was required albeit in a minimal way. These findings address a paucity of studies examining a holistic perspective on sustainability, with previous research on Japanese multinationals tending to adopt an anthropocentric focus. In doing so, with a greater insight into what issues are considered to be corporate sustainability from the multinational enterprises' viewpoint, this research has important implications in informing host country governments developing their policies and regulations to ensure relevant corporate sustainability issues are included. Highlights: Empirical study of key corporate sustainability issues from a management viewpoint. Multi-case study approach with 58 semi-structured interviews. A focus on 16 Japanese multinational enterprises operating in ASEAN. Holistic approach to corporate sustainability addressing paucity of extant research. Host country regulations' critical role in framing corporate sustainability issues.